2006
DOI: 10.1152/physiolgenomics.00010.2006
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of Dyscalc1, the major genetic determinant of dystrophic cardiac calcification in mice

Abstract: Calcification of severely dystrophic muscle is occasionally observed in targeted mouse models of muscular dystrophy and cardiomyopathy. Intracellular calcium deposition occurs in necrotic myocytes in the absence of plasma calcium and phosphate imbalances. In the heart, this recessive trait is referred to as dystrophic cardiac calcinosis (DCC). We identified previously Dyscalc1, a major genetic determinant of DCC, in a 15.2-Mbp region on proximal chromosome 7. We report now further steps toward the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, a single major locus appears to determine the phenotype, as a highly conserved region on chromosome 7 is found in practically all mouse strains that develop DCC (4,9,11). The genotypes of these DCC-positive strains can be compared with those that do not display calcifications upon tissue injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a single major locus appears to determine the phenotype, as a highly conserved region on chromosome 7 is found in practically all mouse strains that develop DCC (4,9,11). The genotypes of these DCC-positive strains can be compared with those that do not display calcifications upon tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Korff et al (11) reported fine mapping of the Dyscalc1 region by analysis of novel congenic mouse strains to an interval Ͻ1 million base pairs (Mb) wide and suggested the ATP-binding cassette C6 (Abcc6) as a new candidate gene for DCC.…”
mentioning
confidence: 99%
“…Altered expression of SPP1 has been found in the dermis of PXE patients analyzed by immunoelectron microscopy (19 ). Recent studies have described strong SPP1 expression due to the Dyscalc1 locus in mice suffering from dystrophic cardiac calcification, with abcc6 gene as a potential candidate gene (20,21 ). The abcc6 gene has just been excluded, however, emphasizing that only the N-terminal part of the gene was screened for sequence variations and that most PXE-associated ABCC6 mutations were found in the C-terminal part (5,6,34 ).…”
Section: Clinical Chemistrymentioning
confidence: 99%
“…SPP1 expression is increased in mice suffering from dystrophic cardiac calcification (20 ), leading to the suggestion that high SPP1 expression is influenced by a trans-activator gene, the Dyscalc1 locus on chromosome 7 (20 ). The mouse abcc6 gene was identified as a potential candidate gene in this region (21 ).…”
mentioning
confidence: 99%
“…PXE has a prevalence of 1 in 25,000 [9] and is characterized by ectopic calcification and fragmentation of elastic fibers of connective tissues, including skin, vascular walls and the eyes [10]. ABCC6 has also been identified as the causal gene within the Dyscalc1 locus that predisposes certain mouse strains (such as C3H/HeJ and DBA/2J) to dystrophic cardiac calcinosis and other ectopic soft tissue calcification [11,12]. …”
Section: Introductionmentioning
confidence: 99%